Smart Cabang Muhammadiyah: Sistem Informasi Kaderisasi untuk Pemberdayaan Organisasi di Sorong Timur - Muh. Mawardi; Muhammad Syahrul Kahar; Muhammad Fathurrahman; Teguh Hidayat Iskandar; Rahmatullah Bin Arsyad; M. Farhan; Nurain Karatlau; Allen Grivits Masombe (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
The management of cadre development within the Muhammadiyah organization requires a structured administrative system to ensure effective and sustainable member development. However, at the Muhammadiyah Sorong Timur Branch, data management was still conducted manually, with about 80% of administrators relying on non-digital records, requiring 15–25 minutes to retrieve a single member's data. This community service aimed to improve organizational capacity through the implementation of a web-based Integrated Cadre Information System accompanied by training and mentoring. The method used a participatory approach, including needs analysis, system implementation, training, and evaluation. The results showed that the system facilitated more efficient and integrated data management. Post-test results of 21 participants showed an average score of 97.6, with 71% achieving perfect scores, indicating a high level of understanding. Interviews also revealed improved administrative efficiency. This activity supports organizational digital transformation through the integration of technology and human resource development.